Strengthening Teacher Capacity through Artificial Intelligence Management Training to Optimize Technology-Based Learning Processes - Wenny Desty Febrian; Bias Yulisa Geni; Muhamad Al Faruq Abdullah (Siber Nusantara Research, 2025)
This community service activity was implemented in response to teachers' limited understanding and skills in managing artificial intelligence as a supporting tool for technology-based learning. This program aims to strengthen teachers' capacity in understanding basic concepts, management strategies, and the implementation of artificial intelligence in the planning, implementation, and evaluation stages of learning. The training was held in Jakarta in December 2025 with 30 participants. The methods used included systematic material delivery, participatory discussions, hands-on practice, and mentoring in developing technology-based learning tools. The results of the activity demonstrated an increase in participants' conceptual understanding and application skills in integrating artificial intelligence into learning activities. Participants were able to develop learning media, design evaluation instruments, and utilize technology more optimally and productively. Thus, the artificial intelligence management training has been proven to have a positive impact on improving teachers' professional competence in supporting the digital transformation process in the field of education.